Analisis Ushuliyyah terhadap Lafaz Ṣarīḥ dan Kināyah dalam Penetapan Hukum Talak Digital - Nur Afifa Maharani; Fatmawati; Zainal Abidin (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The development of digital communication technology has transformed the practice of legal communication in Islamic family law, including the pronouncement of divorce (ṭalāq) through electronic media such as WhatsApp, Telegram, SMS, e-mail, and voice note. This phenomenon raises legal issues concerning the interpretation of divorce expressions, the intention of the speaker (qaṣd al-mutakallim), and the evidentiary value of digital communication. This study aims to analyze the application of the theory of dalālah al-alfāẓ to ṣarīḥ and kināyah expressions in digital divorce, examine the role of qaṣd al-mutakallim and digital qarīnah in determining legal consequences, and explore their implications for evidentiary practices in the Indonesian Religious Courts. This research employs normative legal research using a library research approach. Data were collected from classical works of uṣūl al-fiqh, statutory regulations, and recent scholarly publications, and were analyzed through qualitative content analysis. The findings demonstrate that digital media do not alter the legal classification of divorce expressions because legal validity depends primarily on the clarity of linguistic meaning rather than the communication platform. Explicit (ṣarīḥ) expressions directly produce legal consequences, whereas implicit (kināyah) expressions require proof of the speaker's intention supported by authentic digital qarīnah, including chat histories, metadata, voice recordings, screenshots, and digital forensic evidence. The study concludes that the theory of dalālah al-alfāẓ remains methodologically relevant for interpreting digital divorce while providing a systematic framework that integrates classical Islamic legal theory with contemporary digital evidence in Religious Court proceedings.